2010
DOI: 10.3923/pjbs.2010.51.58
|View full text |Cite
|
Sign up to set email alerts
|

Rooting Response of Five Pomegranate Varieties to Indole Butyric Acid Concentration and Cuttings Age

Abstract: The purpose of this study was to evaluate the effect of cutting age and Indole Butyric Acid (IBA) treatments on five pomegranate varieties propagation by stem cuttings. The experiment was carried out in a partially controlled glasshouse conditions at Mutah University, Jordan. The treatments comprised of two types of cuttings, i.e., hardwood and semi-hardwood; five concentrations of IBA, i.e., 3,000, 6,000, 9,000 and 12,000 ppm as quick dip (10 sec) as well as five Jordanian pomegranate varieties (Kdaree Hello,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…DBS: days before sprouting. Owais (2010) who recommended 20 cm cutting length for optimum propagation of pomegranate. Significantly, similar performance of 10 cm length cuttings with the cuttings of 20 cm length is a valuable result in which number of plants might be doubled by dividing the 20 cm cuttings into two; while at the same time the sprouting percentage of the cuttings would be better.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DBS: days before sprouting. Owais (2010) who recommended 20 cm cutting length for optimum propagation of pomegranate. Significantly, similar performance of 10 cm length cuttings with the cuttings of 20 cm length is a valuable result in which number of plants might be doubled by dividing the 20 cm cuttings into two; while at the same time the sprouting percentage of the cuttings would be better.…”
Section: Resultsmentioning
confidence: 99%
“…The most important problem for cuttings method is the high mortality rate (Sharma et al, 2009) which strongly varies among varieties (Owais, 2010), cutting length, time of the year (Sebastiania and Tognettib, 2004) and cultivation practices applied. It was previously reported that indole-3-butyric acid (IBA) (Sharma et al, 2009;Sarrou et al, 2014), ascorbic acid, gibberellic acid (GA3), hydrogen peroxide (H 2 O 2 ) and melatonin (MEL) (Sarrou et al, 2014) have positive effects on the rooting, root number, root length and shoot length of pomegranate cuttings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in rooting capacity is similar to that found by Pereira et al (2017) in Sequoia sempervirens and other woody species such as Chamaecyparis nootkatensis (Krakowski et al, 2005), Taxus globosa (Muñoz-Gutiérrez et al, 2009) and many others. The clonal variation in rooting capacity is an attribute in many studies on genetic effects (Owais, 2010) and "C" clonal effect; the latter defined as unique physiological or morphological characteristics for the branch (stake) reflecting in its growth environment.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 14 pomegranate landraces were localized in farmers' field, namely; 'Khashaby', 'Khdaree Hello', 'Malesse', 'Bradee Sharabee Asfar', 'Hasmasi', 'Hmaree Hmadee', 'Bradee Sharabee Ahmar', 'Zeklabee', 'Zokom Albagel', 'Khratee', 'Ahmar Hello', 'Khdaree Hmadee', 'Lfani Sharabi', 'Zarori and Esari'. The fourteen Jordanian pomegranate landraces were propagated by stem cuttings according to the conditions proposed by Owais (2010). Thereafter, rooted cuttings were planted in plastic bags to be conserved at Mu'tah University Agricultural Station ex situ.…”
Section: Localization Of Pomegranate Landracesmentioning
confidence: 99%